Signatures of Hong-Ou-Mandel interference at microwave frequencies - Woolley, M. J.; Lang, C.; Wallraff, Andreas J; Blais, Alexandre; Eichler, Christopher (New Journal of Physics, 2013)
Two-photon quantum interference at a beam splitter, commonly known as Hong-Ou-Mandel interference, is a fundamental demonstration of the quantum mechanical nature of electromagnetic fields and a key component of various quantum information processing protocols. The phenomenon was recently demonstrated with microwave-frequency photons by Lang et al (2013 Nature Phys. 9 345-8). This experiment employed circuit QED systems as sources of microwave photons, and was based on the measurement of second-order cross-correlation and auto-correlation functions of the microwave fields at the outputs of the beam splitter using linear detectors. Here we present the calculation of these correlation functions for the cases of inputs corresponding to: (i) trains of pulsed Gaussian or Lorentzian single microwave photons and (ii) resonant fluorescent microwave fields from continuously driven circuit QED systems. In both cases, the signature of two-photon quantum interference is a suppression of the second-order cross-correlation function for small delays. The experiment described in Lang et al (2013) was performed with trains of Lorentzian single photons, and very good agreement with experimental data is obtained. The results are relevant not only to interference experiments using circuit QED systems, but any such setup with highly controllable sources and time-resolved detection. © IOP Publishing and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2022-06-27